ANALISIS PRODUKSI EMISI CO2 BERDASARKAN PRAKIRAAN PEMAKAIAN ENERGI 2008-2030 DI INDONESIA TERHADAP DUNIA - Nurdyastuti, Indyah (BPPT)
An increase on population and income of people will be followed by an increase on the energy utilization. As consequence, the CO2 emission from the energy utilization also increases that has impact on increasing environmental problem. The increase of CO2 emission can be reduced by the utilization environment friendly energy source and technology such as using low carbon energysource and increasing the effi ciency of energy technology. In 2008, most of CO2 emission from energy utilization in the world was contributed from OECDcountries. Most of the CO2 emission from the energy utilization was from electric generation sector. The CO2 emission from energy source is infl uenced by carbon content and combustion system that used in the utilization. Total CO2 emission in the world was almost 33.932 million ton that about 1,3% or 438 million ton was contributed from Indonesia. These emission is estimated to increase in thegrowth rate of 3,5% per year until 2030.Key words: CO2 emission, energy utilization.